A comparative evaluation on the oxidative approaches for extraction of humic acids from low rank coal of Mukah, Sarawak - Sim Siong, Fong; Lau, Seng; Norrafidah, Majri; Haslinda, Mat (Sociedade Brasileira de Qumica, 2007)
Humic acid-based products are well marketed; nevertheless, these products remain unpopular in this region possibly due to the higher selling price resulted from the cost imposed on the imported products. For this reason, it is essential to identify the indigenous source of humic acids as the soil conditioner. Abundant of low rank coals are found in Mukah and the non-energy application of the source are largely unexplored. Preliminary study reported that chemical treatment with nitric acid could potentially increase the essential yield of humic acids from 20% to 85%. Nitric acid is an expensive item, which could add on to the cost, hence possibility of employing other oxidative approaches need to be evaluated. In this study, the humic acids were extracted from the low rank coal of Mukah with HNO3, H2O2 and KMnO4 oxidation and were compared in terms of yield, chemical and spectroscopical characteristics. Results indicated that H2O2 oxidation involved considerable weight losses upon oxidation render it unfavorable for production of humic acids. Potassium permanganate oxidation however was not recommended, as a substantial amount of inorganic compounds was introduced to the products and the essential yield generated was low. Nitric acid oxidation remains the choice of the process for extraction of humic acids as the weight losses involved was acceptable; the yield of humic acids obtained was high with characteristics of low ash content and high acidic functional groups.